Social facilitation within immersive virtual reality enhances perseverance in stroke rehabilitation training - Hadjipanayi, Christos; Sokratous, Dimitris; Kyrlitsias, Christos; Banakou, Domna; Michael-Grigoriou, Despina (Frontiers in Virtual Reality, 2025)
IntroductionIntegrating social interaction into stroke rehabilitation is recommended but often underutilized due to limited resources. Virtual Reality (VR) offers a way to introduce social facilitation via virtual agents in rehabilitation training. Understanding how chronic stroke survivors respond to virtual agents can inform physiotherapy practice with innovative digital tools.MethodsThis study presents five case studies of chronic stroke survivors (2 female, 3 male) with motor impairments, all with paresis of the dominant right upper limb. Participants engaged in a VR-based upper limb exergame under two conditions: playing alone and playing alongside with a virtual agent, acting as a second-player, controlled by a rule-based algorithm. Rehabilitation progress, task performance, and engagement were examined across training sessions.ResultsParticipants who completed all sessions showed consistently higher engagement when playing with a virtual agent compared to playing alone. At the same time, the presence of the virtual co-player had no observable effect on game performance.DiscussionThese findings suggest that incorporating a virtual agent can enhance task engagement and promote perseverance in VR-based stroke rehabilitation. The results are discussed in the context of current VR rehabilitation practices, and implications for clinical practice and future research are outlined.